Pengaruh Model Pembelajaran Problem Based Learning (PBL) Berorientasi Higher Order Thinking Skills (HOTS) Terhadap Hasil Belajar Siswa Kelas XI SMA Negeri 2 Halmahera Selatan Pada Materi Koloid - Abdul Rasid Saraha; St. Hayatun Nur Abu; Dede Ardiansyah (EDUKASI, 2023)
This study aims to find out 1). The Effect of Model Problem Based Learning (PBL) oriented to Higher Order Thinking Skills (HOTS) on the learning outcomes of students of class XI SMA Negeri 2 South Halmahera in colloidal material 2). How big is the influence of the Learning Model Problem Based Learning HOTS oriented (Higher Order Thinking Skills) on the learning outcomes of students of class XI SMA Negeri 2 South Halmahera on colloidal material. This type of research is an experimental study with one group pretest-posttest design. Samples in this study amounted to 22 students. The technique of returning the sample was carried out by purposive sampling technique. The instruments used in this study are test instruments, observation instruments and questionnaires for teacher and student responses. The data obtained subsequently in the analysis using the Pired Samples T Test obtained tcount (14,488)> ttable (1,720) and a significant value of 0.00 <0.05, which shows the influence of the Problem Based Learning (PBL) learning model oriented. Student cognitive learning outcomes with gain values in the experimental class of 0.3 with a medium category.